Postoperative Changes in Tongue Area and Pharyngeal Airway Space following Mandibular Setback Surgery through Intraoral Vertical Ramus Osteotomy - Chen, Kwei-Jing (Biomed Res Int, 2021)
PURPOSE: The aim of this study was to determine changes in the tongue area and pharyngeal airway space (PAS) after intraoral vertical ramus osteotomy (IVRO). MATERIALS AND METHODS: Serial lateral cephalograms of 40 patients with mandibular prognathism who underwent IVRO were evaluated before (T1), immediately after (T2), and more than 1 year after (T3) surgery. Paired t-tests and Pearson's correlation analysis were used to evaluate the postoperative changes in the mandible, nasopharyngeal airway (NOP), retropalatal pharyngeal airway (RPP), retroglossal pharyngeal airway (RGP), hypopharyngeal airway (HOP), PAS, and tongue area (TA). The null hypothesis states that there are no significant correlations among the extent of mandibular setback and the changes in the TA and PAS after IVRO. RESULTS: Immediately after the operation (T12), the mandible was set back by 12.6 mm. The NOP, HOP, and PAS were significantly reduced by 35.7 mm(2), 116 mm(2), and 185 mm(2), respectively. The TA was increased by 69.6 mm(2). The changes in PAS and TA revealed no significant difference between female and male patients at T12, T23, and T13. Moreover, no significant correlations were found among the extent of mandibular setback, TA changes, and PAS changes after IVRO. Thus, the null hypothesis was accepted. CONCLUSIONS: At the final follow-up (T13), no significant change was found in the PAS (including NOP, RPP, RGP, and HOP) and TA. The changes in PAS and TA revealed no significant difference between female and male patients at T12, T23, and T13.